2008
DOI: 10.1038/gt.2008.89
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for improving the transduction efficiency of single-stranded adeno-associated virus vectors in vitro and in vivo

Abstract: Recombinant vectors based on adeno-associated virus type 2 (AAV) target the liver efficiently, but the transgene expression is limited to B5% of murine hepatocytes. Viral second-strand DNA synthesis continues to be a rate-limiting step for efficient transduction by the single-stranded AAV (ssAAV) vectors. This is due, in part, to the presence of a cellular chaperone (FK506-binding) protein, FKBP52, phosphorylated forms of which interact with the D-sequence in the inverted terminal repeats of AAV2 genome and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
42
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 42 publications
6
42
0
Order By: Relevance
“…23 Under conditions of limited phosphorylatation of capsid following cellular entry, vector performance improves because of reduced ubiquitination and proteasomal degradation. [34][35][36]46 Here, we find that capsids engineered to minimize tyrosine phosphorylation are also less presented to CD8 1 T cells. At…”
Section: Ctl-mediated Killing Is Less Efficient Against Hepatocytes Tmentioning
confidence: 83%
“…23 Under conditions of limited phosphorylatation of capsid following cellular entry, vector performance improves because of reduced ubiquitination and proteasomal degradation. [34][35][36]46 Here, we find that capsids engineered to minimize tyrosine phosphorylation are also less presented to CD8 1 T cells. At…”
Section: Ctl-mediated Killing Is Less Efficient Against Hepatocytes Tmentioning
confidence: 83%
“…10) significantly improved transduction of AAV vectors in the AAV2 serotype background. They showed that phosphorylation of these tyrosines was prevented by their conversion to phenylalanine and that this reduced the loss of input capsids due to proteolytic degradation (27)(28)(29). We would suggest that it may also be possible that phosphorylation of these tyrosines …”
Section: Discussionmentioning
confidence: 99%
“…Augmented transgene expression from ssAAV2 vectors also occurs in transgenic mice overexpressing TC-PTP (Qing et al, 2003), and in mice deficient in FKBP52 (Zhong et al, 2004b). Subsequently, we have also developed scAAV-TC-PTP and scAAV-PP5 vectors (Zhong et al, 2004a;Zhao et al, 2007;Jayandharan et al, 2008). We reasoned that if scAAV-TC-PTP and scAAV-PP5 vectors are admixed with a conventional ssAAV vector before transduction, the rapid and simultaneous expression of TC-PTP and PP5 from scAAV vectors, which do not require viral second-strand DNA synthesis, would completely dephosphorylate FKBP52 at both tyrosine and serine=threonine residues, respectively.…”
mentioning
confidence: 99%
“…This would lead to more efficient second-strand DNA synthesis of the ssAAV vector, resulting in high-efficiency transgene expression. Indeed, this coadministration strategy led to an *16-fold increase in the transduction efficiency of ssAAV2 vectors in primary murine hepatocytes in vivo ( Jayandharan et al, 2008).…”
mentioning
confidence: 99%